NICKELS & DIMES HOW SALES & EXCISE TAXES ADD UP IN THE 50 STATES (Tufts Archival Research Center, 2007)
Report put out by the Citizens for Tax Justice in 1988 regarding a study showing the way regressive taxes unfairly tax lower income people. Suggests ways in which the states can close the inequality gaps in their tax implementation. Includes detailed tax data on all fifty states.